PERBEDAAN PARAMETER KARDIO PULMONAL SETELAH TINDAKAN OPEN SUCTION - Muhamat Nofiyanto (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Endotracheal suctioning is often performed by nurses and beneficial for critically ill patients. Suctioning is essential for removing secretions, maintaining airway patency and prevent unexpected complications. Open suctioning is performed by disconnecting patients with the ventilator. Suctioning not only removed secretions in the airway but also oxygen. Suctioning must be done correctly, safely, effectively and efficiently to prevent unexpected events in critically ill patients. Objective: This study aimed to determine differences on cardiopulmonary parameters after open suction in critically ill patients Methods: The study design was comparatif cross sectional analytic approach, using one group pre test and post test. The sample of the research amounted to 34 people, using purposive sampling technique. Catheter size 14 Fr on ETT number 7 mm used in this research to performed endotracheal suctioning. Cardiopulmonary parameters (Heart rate/ HR, respiratory rate/RR, oxygen saturation/SpO2, systolic blood pressure/ SBP and diastolic blood pressure/DBP) measured by pulse oxymeter and bedside monitor before suction and immediately thereafter. Results: The results showed increase average heart rate 6.412 (from 106.62 into 113.03), Respiratory rate has increased 4.971 (from 20.62 into 25.59), SpO2 decreased 1.68 (from 99.09 into 97.41), and systolic blood pressure increased 5.71 (from 118.29 into 124.00) after performed open suction. The results of paired t-test statistical analysis (for RR, HR) obtained a < 0.05 (0.000), whereas Wilcoxon statistical analysis (for SpO2, SBP) obtained a < 0.05 (0.000 and 0.001). So it can be said that the difference cardiopulmonary parameters was statistically significant after perfomed open suction in critically ill patients. Keywords: Endotracheal suctioning, cardiopulmonary parameters, critically ill patients.